Kinky choices, dictators and split might: A non-cooperative model for household consumption and labor supply - Jan Boone; Karen der Wiel; Arthur Soest; Frederic Vermeulen (IZA Journal of Labor Economics, 2014)
We model consumption and labor supply behavior of a couple in a non-cooperative setting. Using minimal assumptions, we prove that demand for public goods is characterized by three regimes. It is either determined by the preferences of one of the partners only (Husband Dictatorship or Wife Dictatorship), or by both spouses' preferences, in which case each partner's influence depends on the relative wage rates (Split Might). The model is illustrated empirically using a sample drawn from the Consumer Expenditure Survey (CEX) where expenditures on children's goods are a public good in both spouses' preferences. It turns out that the spending pattern reflects the husband's preferences in about 54% of the couples in our sample. Still, in about 45% of the households, the wife acts as a dictator. Somewhat less than 1% of the couples is characterized by a split might regime.
Keywords: D11; D12; D13; 330; Consumption; Labor supply; Intra-household allocation; Non-cooperative model; Public goods